Phenolics from Archidendron clypearia (Jack) I.C.Nielsen protect SH-SY5Y cells against H2O2-induced oxidative stress. (August 2020) - Wang, Yu-Xi; Han, Feng-Ying; Duan, Zhi-Kang; Chang, Ye; Lin, Bin; Wang, Xiao-Bo; Huang, Xiao-Xiao; Yao, Guo-Dong; Song, Shao-Jiang
Abstract: Five undescribed phenolics named pithecellobiumin C-G, along with thirteen known ones were isolated from the twigs and leaves of Archidendron clypearia (Jack) I.C.Nielsen. Their structures were elucidated based on comprehensive spectroscopic analyses, combined with computer-assisted structure elucidation software (ACD/Structure Elucidator) and gauge-independent atomic orbitals (GIAO) NMR chemical shift calculations. The absolute configurations were determined by comparison of experimental and calculated specific rotation and ECD curves. These compounds were tested for their neuroprotective activities against H2 O2 -induced injury in human neuroblastoma SH-SY5Y cells by MTT assay. Pithecellobiumin C-E exhibited noticeable neuroprotective effect. Further pharmacological study demonstrated that they could prevent cell death through inhibiting the apoptosis induction. Flow cytometry assays also proved that these compounds could attenuate reactive oxygen species (ROS) level and mitochondrial dysfunction in SH-SY5Y cells. Graphical abstract: Image 1 Highlights: Five undescribed galloylated phenolics (pithecellobiumin C-G) and thirteen known compounds were isolated from A. clypearia. Synergistic combination of CASE and DFT methods has been used to determine the gross structures and the absolute configurations. Pithecellobiumin C-E probably exerted neuroprotective activity through reducing the level of reactive oxygen species and inhibiting mitochondria damage in SH-SY5Y cells.